Dephrasal adjectives in Polish – A case of syntax-inside-morphology - Joanna Kolbusz-Buda (LingBaW)
The present paper is part of a larger project which investigates the issue of “syntax-inside-morphology” in the domain of Polish word-formation. In what follows, we explore the thus far unstudied territory of dephrasal adjectives, such as tużpopołudniowy ‘right-after-noon’ and ponadstustronicowy ‘over-one-hundred-page’ built on phrasal bases subjected to suffixation.